Аналіз та вдосконалення роботи систем освітлення основних загальнопромислових виробництв - Главнов, Ігор Вікторович; Hlavnov, Ihor (ЦНТУ, 2024)
Об’єктом досліджень є система суміщеного освітлення ремонтно-механічного цеха. Предмет досліджень являється підвищення ефективності системи освітлення за рахунок впровадження енергоощадних заходів. Метою роботи є аналіз та вдосконалення роботи системи освітлення основних загальнопромислових виробництв на прикладі ремонтно-механічного цеху. У першій главі кваліфікаційної роботи виконано аналіз сучасних систем освітлення та розглянуті основні напрямки підвищення ефективності їх роботи. Друга глава присвячена модернізації системи освітлення РМЦ, виконані світлотехнічні та електротехнічні розрахунки. У третій главі досліджені сучасні програми світлотехнічних розрахунків та виконано моделювання системи освітлення механічного відділення РМЦ у програмі «DIALux». Четверта глава розкриває комплексний підхід до вдосконалення системи освітлення цеху, розрахована економічна ефективність застосованих заходів. У п’ятій главі висвітлені заходи з охорони праці при монтажі та експлуатації системи освітлення РМЦ. The object of research is the combined lighting system of the repair and mechanical workshop. The subject of research is improving the efficiency of the lighting system due to the implementation of energy-saving measures. The purpose of the work is to analyze and improve the operation of the lighting system of the main general industrial productions using the example of a repair and mechanical shop. In the first chapter of the qualification work, an analysis of modern lighting systems was carried out and the main directions for improving the efficiency of their work were considered. The second chapter is dedicated to the modernization of the repair and mechanical shop lighting system, lighting and electrical calculations have been performed. In the third chapter, modern programs for light engineering calculations are studied and modeling of the lighting system of the mechanical department of the repair and mechanical shop in the "DIALux" program is implemented. The fourth chapter reveals a comprehensive approach to the improvement of the lighting system of the shop, calculated economic efficiency of the applied measures. The fifth chapter covers labor protection measures during the installation and operation of the repair and mechanical shop lighting system.
Analysis and improvement of lighting systems of the main general industrial productions
Keywords: освітлювальна установка; джерело світла; світлодіодний світильник; моделювання освітлення; ефективність системи освітлення; lighting installation; light source; LED lamp; lighting simulation; lighting system efficiency